Crohn's disease after multiple doses of rituximab treatment in a child with refractory nephrotic syndrome and an ATG2A mutation: a case report - Shi, Kaili; Fu, Mengzhen; Xia, Wei; Zhang, Pei; Gao, Chunlin; Xia, Zhengkun (Frontiers in Pediatrics, 2024)
De novo inflammatory bowel disease (IBD) in response to rituximab (RTX) has been documented on multiple occasions as a severe adverse effect. However, none of these reports mentioned any genetic variation associated with this complication. We describe the case of a 16-year-old patient with refractory nephrotic syndrome (NS) diagnosed at the age of 6 years, notably with a heterozygous mutation of the ATG2A gene, who developed Crohn's disease (CD) following ten administrations of RTX. Seventy months after the first and six months after the last RTX dose, the patient developed recurrent abdominal pain, hematochezia, oral aphthous ulcers and weight loss. On the basis of clinical evaluation and ileo-colonoscopy findings, the patient was diagnosed with CD and treated with mesalazine. A significant amelioration of clinical symptoms was achieved after 11 days of mesalazine treatment. A repeat ileo-colonoscopy performed four months later revealed nearcomplete resolution of the ulcers and marked mucosal healing. The underlying pathophysiology of RTX-induced IBD has not yet been clarified. Autophagy associated with ATG2A mutation is likely involved in the pathogenesis. This case underscores the need for vigilance in monitoring children with NS with gastrointestinal symptoms following RTX treatment, especially those who have hereditary susceptibility and have received multiple administrations.